Cyclic behaviour of uncorroded and corroded steel reinforcing bars. (1st February 2015) - Caprili, Silvia; Salvatore, Walter
Highlights: Analysis of the mechanical properties of different reinforcing steels under monotonic loads. Analysis of the low-cycle fatigue (LCF) behaviour of different typologies of reinforcements. Influence of corrosion on the monotonic behaviour of bars, in terms of strength and ductility. Analysis of the combined effects of corrosion phenomena and low-cycle fatigue. Influence of production process on the ductile behaviour of bars. Abstract: In the present work the results of a wide experimental test campaign on steel reinforcing bars, including monotonic tensile and low-cycle fatigue tests, the last ones able to reproduce the stress–strain condition induced by seismic events, are presented. The main aim of the research work consists in the analysis of the combined effects of seismic action and aggressive environmental conditions on the ductile behaviour of steel reinforcements: as a consequence, mechanical tests were executed also on samples previously subjected to exposure in salt spray chamber, evaluating the residual mechanical properties and dissipative capacity.